2018
DOI: 10.7554/elife.39440
|View full text |Cite
|
Sign up to set email alerts
|

Myosin V functions as a vesicle tether at the plasma membrane to control neurotransmitter release in central synapses

Abstract: Synaptic vesicle fusion occurs at specialized release sites at the active zone. How refilling of release sites with new vesicles is regulated in central synapses remains poorly understood. Using nanoscale-resolution detection of individual release events in rat hippocampal synapses we found that inhibition of myosin V, the predominant vesicle-associated motor, strongly reduced refilling of the release sites during repetitive stimulation. Single-vesicle tracking revealed that recycling vesicles continuously shu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 63 publications
13
69
1
Order By: Relevance
“…Among other mechanisms, it has been shown that myosin-Va associates to the ER and binds to the ryanodine calcium receptor channels on the ER membrane, and also responds to ER-derived calcium by associating with vesicles and directing them to specific sites 50 . More recently, myosin-Va was shown to tether synaptic vesicles to the plasma membrane near Ca +2 influx sites and help to increase the retention of vesicles at the release site 51 . The decrease in the ER-mitochondrial contact surface, observed here in myosin-Va knockdown cells, is also consistent with a calcium triggered-role for myosin-Va at the ER-mitochondrial interface.…”
Section: Discussionmentioning
confidence: 99%
“…Among other mechanisms, it has been shown that myosin-Va associates to the ER and binds to the ryanodine calcium receptor channels on the ER membrane, and also responds to ER-derived calcium by associating with vesicles and directing them to specific sites 50 . More recently, myosin-Va was shown to tether synaptic vesicles to the plasma membrane near Ca +2 influx sites and help to increase the retention of vesicles at the release site 51 . The decrease in the ER-mitochondrial contact surface, observed here in myosin-Va knockdown cells, is also consistent with a calcium triggered-role for myosin-Va at the ER-mitochondrial interface.…”
Section: Discussionmentioning
confidence: 99%
“…Can factors other than desynchronization contribute to the difference in amplitude within MVR events and its spatial arrangement relative to the AZ center, such as differences in vesicle size or cleft pH along the AZ plane? We used the Large-Area Scanning Electron Microscopy (LaSEM) micrographs of our cultures (Maschi et al, 2018) to determine the size of all vesicles positioned next to the AZ (within 100nm, defined previously as tethered vesicles (Maschi et al, 2018a)) as a function of distance to the AZ center. Vesicle diameter did not exhibit any measurable changes with distance from the AZ center (Figure S3C,D).…”
Section: Temporal Desynchronization Of Release Events Comprising Mvrmentioning
confidence: 99%
“…LASEM methods and data used were published previously (Maschi et al, 2018). Briefly, cells were grown on 12 mm glass coverslips, were aspirated of media and fixed in a solution containing 2.5% glutaraldehyde and 2% paraformaldehyde in 0.15 M cacodylate buffer with 2 mM CaCl2, pH 7.4 that had been warmed to 37˚C for one hour.…”
Section: Fluorescence Microscopymentioning
confidence: 99%
See 2 more Smart Citations